Analisis Keberlanjutan Program Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat (PAMSIMAS) di Kecamatan Mersam Kabupaten Batanghari Provinsi Jambi - Adinda Putri Kayama; Anis Tatik Maryani; Suryono Suryono (Universitas Batanghari Jambi, 2023)
PAMSIMAS (Community-Based Water Supply and Sanitation) is one of the PNPM (National Community Empowerment Program) to create clean and healthy living communities through the provision of community-based clean water and drinking water and community-based sanitation. The aims of this research are 1) describe the description of the characteristics in the implementation of the PAMSIMAS program in Mersam District, Batanghari Regency in 2022; 2) evaluate success in sustaining the PAMSIMAS program in Mersam District, Batanghari Regency, and 3) find out the relationship between age, gender, education, employment status and income in the sustainability of the PAMSIMAS program in Mersam Subdistrict, Batanghari Regency. This type of research is quantitative and qualitative research with a total sample of 358 respondents spread over 4 PAMSIMAS program beneficiary villages. The research was conducted in Mersam District, Batanghari Regency. The data were analyzed using the Chi-Square test. The research results show 1) there are differences in the frequency of the results of interviews with respondents in the four villages in Mersam District; 2) the success of the program was only successful in Sungai Puar Village with an assessment percentage of 51.19%; and 3) There is a relationship between income and program sustainability in Sengkati Mudo Village, there is a relationship between employment status and program sustainability in Seangkati Baru Village, there is a relationship between age and employment status and program success in Seangkati Kecil Village, and there is a relationship between education and program success in Sungai Puar Village. Therefore, to maximize the sustainability of the program, the government must pay attention to the sustainability aspects of the program and how to build the community to become managers of these facilities. The concern that arises from the community must also be fully focused on increasing the sustainability of the program.